Effect of CMC degree of substitution and gliadin/CMC ratio on surface rheology and foaming behavior of gliadin/CMC nanoparticles. (October 2020) - Peng, Dengfeng; Jin, Weiping; Arts, Miriam; Yang, Jack; Li, Bin; Sagis, Leonard M.C.
Abstract: To understand the influence of the degree of substitution (DS) of sodium carboxymethyl cellulose (CMC) and gliadin:CMC ratio on the surface and foaming behaviors of gliadin-CMC nanoparticles (G-CMC NPs) at pH 3, three DS (0.7–1.2) and four ratios (G:CMC~1:0.5–1:2) were investigated. Gliadin NPs with a pH of 3 were utilized as a control. Results showed that G-CMC NPs at all investigated DS and ratios possessed higher foamability and foam stability when compared to the control. This indicated that adding CMC to gliadin NP suspensions could greatly improve their foaming properties. G-CMC NPs with a DS of 0.7 and 0.9, had lower surface charge than G-CMC1.2 NPs, resulting in a weaker electrostatic repulsion, thus leading to faster adsorption kinetics and higher foamability. By increasing the G:CMC ratio from 1:0.5 to 1:2, the particle size gradually rose, and the zeta potential remained unchanged. At a ratio of 1:2, the highest foam stability was observed. This might be ascribed to the high continuous phase viscosity at this ratio, which could slow down the drainage rate and protect the bubbles against coalescence and disproportionation. It was worth mentioning that G-CMC NPs at all ratios exhibited impressive foamability (~220%) even at a very low concentration of G-CMC NPs (gliadin was fixed at 1 mg/mL). This implies that G-CMC NPs could act as a new efficient foaming agent, and based on its simple preparation, have the potential to be widely applied in foamed food. Graphical abstract: Image 1 Highlights: Gliadin-CMC NPs at all DS and ratios possessed better foaming behavior than gliadin NPs. Gliadin-CMC NPs at all ratios displayed impressive foamability (~220%). Absorption rate of G-CMC NPs was governed by the surface charge of the NPs.